PENERAPAN DISCREPANCY EVALUATION MODEL DALAM EVALUASI PROGRAM PENDIDIKAN INKLUSIF DI SDN SUNGAI MIAI 5 BANJARMASIN - Alpha Ariani (Universitas Achmad Yani Banjarmasin, 2019)
The research aimed to evaluate the implementation of an inclusive education program in the elementary school. This research uses a qualitative approach, an evaluation method with a discrepancy evaluation model (DEM) which has four stages: design, installation, process, and results. Data collection techniques used observation, interviews, documentation studies, and questionnaires. The results of the study show: 1) the program has not been designed according to criteria and standards; 2) there are many implementation of supporting resources that do not fit the criteria and standards; 3) implementation in the form of activities is still not optimal; and 4) program products do not reflect the achievement of the objectives of the program. Based on these findings,it is necessary to improvement, seriously, and increase as much as possible in all aspects so that services and learning in inclusive schools are more qualified.